Evaluation of estimates of alveolar gas exchange by using a tidally ventilated nonhomogenous lung model. - Busso, T; Robbins, P (1997)
The purpose of this study was to evaluate algorithms for estimating O2 and CO2 transfer at the pulmonary capillaries by use of a nine-compartment tidally ventilated lung model that incorporated inhomogeneities in ventilation-to-volume and ventilation-to-perfusion ratios. Breath-to-breath O2 and CO2 exchange at the capillary level and at the mouth were simulated by using realistic cyclical breathing patterns to drive the model, derived from 40-min recordings in six resting subjects. The SD of the breath-by-breath gas exchange at the mouth around the value at the pulmonary capillaries was 59.7 +/- 25.5% for O2 and 22.3 +/- 10.4% for CO2. Algorithms including corrections for changes in alveolar volume and for changes in alveolar gas composition improved the estimates of pulmonary exchange, reducing the SD to 20.8 +/- 10.4% for O2 and 15.2 +/- 5.8% for CO2. The remaining imprecision of the estimates arose almost entirely from using end-tidal measurements to estimate the breath-to-breath changes in end-expiratory alveolar gas concentration. The results led us to suggest an alternative method that does not use changes in end-tidal partial pressures as explicit estimates of the changes in alveolar gas concentration. The proposed method yielded significant improvements in estimation for the model data of this study.